To Detach or Not to Detach? Two Experimental Studies on the Affective Consequences of Detaching From Work During Non-work Time - Sonnentag, Sabine; Niessen, Cornelia (Frontiers in Psychology, 2020)
Previous correlational studies have shown that both psychological detachment from work and positively thinking about work during non-work time are associated with favorable affective states. In our research we integrate these contradictory findings and add more rigor to detachment research by using an experimental design. In two experimental studies conducted in the laboratory, we manipulated two different kinds of detachment from work (thinking about a hobby; explicit detachment instruction) and three different kinds of thinking about work (thinking negatively, thinking positively, thinking in an unspecific way) by short written instructions. Results show that both detachment strategies lead to a reduction in negative affect (in both studies) and to an increase in positive affect (in one study). The effect of detachment was particularly strong when it was contrasted with thinking negatively about work and when end-of-workday negative affect was high. In some of the comparisons, the affective benefits of positively thinking about work were stronger than those of psychological detachment from work. Taken together, our studies demonstrate that detachment from work as well as positive thinking improves subsequent affect, highlighting the causality underlying the association between psychological detachment from work – as a core recovery experience – and subsequent affective states.